#TITLE_ALTERNATIVE# - MUSTAQIEM (NIM 13602041), FIKI
Analysis of flow around cylinder is the classical aerodynamic problem often to study. There are some phenomena that occur in the flow around cylinder, some of them are: vortex shedding, Von Karman vortex, vortex induced vibration and lift generation at cylinder with circulation. This research studies the numerical model that can capture the entire phenomenon in incompressible, viscous, steady and unsteady condition. And studying flow around oscillating cylinder in quasi-steady flow. This experimental model is using Reynolds number, viscosity model and solution control as the parameters. The result in the steady flow test is use as the base test in unsteady and quasi-steady case. Unsteady test performed in flow around cylinder with circulation. Quasi-steady test performed in flow around oscillating cylinder. The unsteady results is use for studying the connection between separation of vortex and rotational speed, Quasi-steady results is use for studying the connection between frequency of vortex separation with motion of cylinder.